Prosedur Pembayaran Pajak Kendaraan Bermotor Pada Kantor Samsat Kabupaten Rokan Hilir Riau - Isnaini Husna; Suhairi Suhairi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Motor Vehicle Tax (PKB) is the administration of a regional tax on motorized vehicles. The object of the motor vehicle tax is proof of ownership or power over a motor vehicle, while the subject of the motor vehicle tax is an individual or entity that owns or controls a motor vehicle. The purpose of this research is to find out the procedures for the implementation of motor vehicle tax payments at the samsat bagan sinembah office, to find out the sanctions or fines applied by the tax authorities to taxpayers who do not fulfill their tax obligations in the motor vehicle tax. The type of research in this study uses descriptive qualitative research with data collection and observation techniques. Downstream. Where the UPTD has the task of collecting Motor Vehicle Taxes regulated in Riau Governor Regulation Number 08 of 2012 concerning Instructions for Implementing Motor Vehicle Taxes (PKB) and Motor Vehicle Transfer Fees (BBN-KB), Making efforts in dealing with obstacles that arise by and in order to further increase the number of Motor Vehicle Tax Collection every year.